(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1997)
Conodonts (62 species and subspecies) from acid-leaching of 226 samples from four sections through the Ali Masjid Formation west of Misri Khel in the former South Khyber Agency, north-west Pakistan, are documented by illustrations and distributional data. These indicate that most of this unit, at least in that area, spans the interval Middle crepida Zone (low in the Famennian) to at least Early crenulata Zone (mid-Tournaisian), though a fauna from low in one of the sections produced conodonts indicative of the Late falsiovalis Zone (early Frasnian). Two major hiatuses are inferred: between the Late falsiovalis and Middle crepida zones, and between the Late expansa and Early duplicata zones. Coherence of the conodont biostratigraphy accords with lithologic alignments between the sections.